An easy and novel method for safer brachytherapy: real-time fluoroscopic verification of high-dose-rate 192Ir source position using a flat-panel detector. (24th April 2019) - Nose, Takayuki; Masui, Koji; Takenaka, Tadashi; Yamazaki, Hideya; Nakata, Katsuya; Otani, Yuki; Kumita, Shinichiro
Abstract: Real-time fluoroscopic verification of the active source position during actual treatment is the only established method to prevent high-dose-rate (HDR) brachytherapy events. The challenge is spurious signals from an HDR 192 Ir source that result in image halation, making source positions indiscernible when using a non-modified image intensifier fluoroscope. We have previously reported a method for observing an HDR 192 Ir source by using an elaborately modified image intensifier system. The newly developed flat-panel detector fluoroscope is, by contrast, inherently halation-free thanks to the wider dynamic range (12–14 bits), compared with image intensifier fluoroscopes (8 bits). To explore the feasibility, we applied a commercially available flat-panel detector fluoroscope without modification to actual treatment. We successfully observed source positions without halation for all 107 patients, with a total of 522 HDR treatment sessions during a 3-year period from 2014 to 2017. Actual source positions were compared with planned positions on the planning hard copy. With this method, we detected a total of 1 error (0.2%) among the 522 sessions, at a similar detection rate of 0.1% with our previous experience using a modified image intensifier fluoroscope. We found that a commercially available flat-panel detector fluoroscope is ready for use for real-time verification and outweighs the need for elaborate modifications of an image intensifier fluoroscope. A flat-panel detector fluoroscope will help the global radiation oncology community promote real-time verification programs, leading to safer HDR brachytherapy.